Економічна сутність витрат та їх визнання відповідно до потреб обліку та управління - Костякова, Анна Анатоліївна; Костякова, Анна Анатолиевна; Kostyakova, Anna (My University, 2016)
EN: In the article the essence of concepts "costs", "expenses" and their consistency from the point of view of existing normative-legal acts of state and General economic literature. A study of the recognition of the concept of "costs" in accordance with the requirements of financial and management accounting. UK: В статті розглянуто сутність понять «витрати»/«затраты», «издержки» та їх взаємоузгодженість з точки зору діючих нормативно-правових актів держави та загально - економічної літератури. Проведено дослідження визнання поняття «витрати» відповідно до потреб фінансового та управлінського обліку.
Economic concept of costs and their recognition in accordance with the requirements of accounting and management
Keywords: costs; expenses; income; process activity; the time factor; затрати; витрати; доход; процес діяльності; фактор часу